Adventure Mode: A Speculative Rideshare Design - Sherman, Stephanie; Smith, Ash Eliza; Forster, Deborah; Emmenegger, Colleen (Frontiers in Computer Science, 2021)
Most smart city projections presume transportation efficiency, predictability, and control as core design principles. Adventure Mode is a speculative game developed as part of a research project with a major automotive company, designed to challenge presumptions about the uses for and interactions between humans and moving vehicles in a smart city environment. Adventure Mode reframes the possible uses of moving vehicles from destination-based to journey-based experiences, embracing the submission to algorithmic decision as a ludic modality in human-computer interactions and Urban Artificial Intelligence proposals. Adventure Mode pushes the probabilities for unexpected encounters and anonymous play in increasingly predictable and disclosed environments.